2022
DOI: 10.1111/eth.13260
|View full text |Cite
|
Sign up to set email alerts
|

Aggression‐based social learning in the zebra finch (Taeniopygia guttata)

Abstract: Selectively learning from specific types of individuals may be adaptive if demonstrator characteristics can be used to identify more beneficial sources of social information.Such "social learning biases" have been experimentally demonstrated in a number of species, but these experiments generally involve restricted laboratory conditions using a limited number of potential demonstrators and tend to consider only the characteristics of demonstrators rather than the importance of pairwise relationships on informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The abovementioned procedures should be taken into careful consideration when planning experiments because of the extensive amount of research effort involved. Only one record did not implement a learning phase because the test was recorded and analysed for the entire duration (Easter et al 2022 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abovementioned procedures should be taken into careful consideration when planning experiments because of the extensive amount of research effort involved. Only one record did not implement a learning phase because the test was recorded and analysed for the entire duration (Easter et al 2022 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Behaviours demonstrated by live or video-recorded birds include nest-building and foraging using specific coloured materials and lid removal. A computer-controlled feeding apparatus may also be used to assess the learning between partners through foraging scans Demonstration of foraging: (Benskin et al 2002 ; Camacho-Alpízar et al 2021 ; Guillette et al 2014 , 2022 ; Guillette and Healy 2014 , 2017 ; Katz and Lachlan 2003 ; Larose and Dubois 2011 ; Mora and Forstmeier 2014 ; Osbrink et al 2021 ; Riebel et al 2012 ; Templeton et al 2017 ; Van Leeuwen et al 2021 ); demonstration of nest-building: Breen et al 2019 ; Guillette et al 2016 ; Guillette and Healy 2019 ; Lid removal: Easter et al 2022 ; Farine et al 2015 ; foraging scan: Beauchamp and Kacelnik 1991 Spatial learning Spatial learning tests are used to assess a subject’s ability to recognise the location of the correct feeder based on environmental cues (e.g. surrounding and distant objects).…”
Section: Introductionmentioning
confidence: 99%
“…After the experiment, participants completed a post-study questionnaire, used to gather information about individual characteristics that may influence social information use, including age and gender. As prior research has indicated that aggression may play a role in social learning (Bandura et al, 1961;Easter et al, 2022), we also obtained self-assessed aggression scores for each participant, using Bryant and Smith's (2001) aggression questionnaire, to investigate whether aggression levels influenced social information use in our study. We also considered that a participant's tendency to play video games may influence their general behaviour within VERSEe.g.…”
Section: Post-study Questionnairementioning
confidence: 99%